MANAJEMEN KEARSIPAN PADA PERUSAHAAN X - Septia Claudia, Sella; Wiradendi Wolor, Christian; Suherdi, Suherdi (Transpublika Publisher, 2023)
Archive management as archive storage, which is the process of maintaining and securing company records or records, in the success of records management must run on a process that includes classification, creation, receipt, and maintenance of records. This study aims to determine the archive storage system, guidelines for lending archives and obstacles to borrowing archives. This study uses a qualitative method in a descriptive form with a case study approach. The subjects in this study were 4 (four) people using a purposive sampling technique. The results of the study show that there are two archive storage systems in Company X, namely, active archives and inactive archives. Borrowing archives is in accordance with applicable procedures, however, problems in the borrowing of archives still often occur because in the procedure there is no period of time for borrowing archives, this makes employees forget about returning archives and lack of employee awareness of the importance of archives.